Investigating the moral behaviour of public transport users in returning lost but found items - Simon Ahumah Ocansey; Gideon Link Sackitey; Makafui Agboyi (Urban, Planning and Transport Research)
This paper aims to explore the likelihood of lost items to be recovered by public transport (PT) users with a focus on the moral values of other PT users in the city of Accra. To achieve this goal, a non-experimental research design was employed to identify the factors influencing PT users’ decisions to return lost items. Data were collected using a revealed preference survey (RP), which was distributed both manually and online using Google Form. The survey consisted of a structured questionnaire with close-ended questions. A total of 603 respondents completed the survey, and the reliability of the questionnaire was verified using Cronbach’s Alpha (CA), yielding a score of 0.804. The study’s findings revealed that religious values (Mean = 4.41, SD = 1.97) and empathy (Mean = 4.37, SD = 1.92) were the two most significant factors that influenced respondents’ decisions to return lost items. Regarding the ‘value of an item’, the high standard deviation indicates that respondents’ perceptions of an item’s value varied greatly and may not have affected respondents decision to return lost but found item. Future research in urban transportation should concentrate on experimental research where reflection of respondents’ true decision to return or keep a found item can be ascertained.